Estudo e desenvolvimento de prótese de tornozelo usando atuador com memória de forma - Oliveira, Samuel de (2019)
This research paper presents the study and development of an ankle prosthesis prototype using shape memory alloy actuators. The actuators, mounted as series linear actuators, made it possible to change torque characteristics over the ankle to complement the walking movement. With its action, the mechanical springs in the prototype store energy during the second phase of walking support, returning the energy in the third phase, boosting the amputee. For the design of the structure, anthropometric dimensions were used from measurements made on a human skeleton normalized to an average size of a Brazilian human foot. Dynamic and kinematic calculations of the prototype were developed to dimension the prosthesis structure, stainless steel mechanical springs and shape memory alloy springs (actuators). The prototype was made of ABS plastic by rapid prototyping with some parts made of stainless steel. Since the ankle torque pattern has its values normalized in the literature, it was possible to calculate the ankle torque with the proposed structure, perform experimental tests and compare the obtained values. The experimental results were promising to obtain the characteristic torque and the prototype capacity to store and return energy during walking. As a scientific contribution, the prosthesis walking graph was compared with the human pattern and with some results from other authors.